Comparison of Mesh Type Seismic Retrofitting for Masonry Structures - Nissanka, N.A.A.C.; Priyankara, R.L.S.; Sathiparan, N. (My University, 2015)
The tremendous loss of life that resulted in the aftermath of recent earthquakes in developing countries is mostly due to the collapse of non-engineered building structures. It has been observed that these buildings cannot withstand the lateral loads imposed by an earthquake and often fails, in a brittle manner. This underscores the urgency to find simple and economic solutions to reinforce these buildings. Different conventional retrofitting techniques are available to increase the strength and/or ductility of unreinforced masonry walls. Recent years, several researches work on mesh type retrofitting for masonry structures to delay or prevent the collapse of buildings and reduce the number of lives lost during devastating earthquake events. This paper reviews and discusses the state-of-the-art on seismic retrofitting of masonry walls with emphasis on the mesh type retrofitting techniques include retrofitting procedures, cost, improvement in structural performance and limitations.
Keywords: Masonry; retrofitting